Stress and Quality of Life in the educational context during the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: Cross-sectional observational epidemiological study that aimed to assess the level of stress and the QoL of teachers and students at a Federal Teaching Institute, in the context of the COVID-19 pandemic. Method: Data collection was performed remotely with the aid of Google Forms®, using the Lipp Stress Symptoms Inventory (ISSL), the World Health Organization Quality of Life (WHOQOL-bref) and a sociodemographic questionnaire. The analysis of the ISSL and WHOQOL-bref data took place according to the standardization elaborated by the authors of the instruments, and the sociodemographic data were analyzed using descriptive and inferential statistics. Results: 259 individuals participated, of which 54.83% had scores compatible with stress, predominantly in the resistance phase (52.82%). The general quality of life index was 65.11% and the “Environment” domain had the best evaluation (13.78 ± 2.39). An association was evidenced between low quality of life and stress (OR 3.13; CI 95%), as well as between school routine and stress (OR 2.93; CI 95%). Marital status (p = 0.041), race (p = 0.043), category (p = 0.011) and children (p = 0.042) were significantly associated with quality of life. Conclusion: It was evident that low quality of life and school routine were significantly associated with stress.